Caracterización del perfil emprendedor del estudiante de las facultades de administración y afines, adscritas al Capítulo Oriente de la Asociación Colombiana de Facultades de Administración (Ascolfa) y a la Red de Investigadores (Riaco), fase I - Albornoz Silva, María Jenny (Universidad de San Buenaventura - Cali, 2017)
The network of researchers of Ascolfa-Riaco, made up of the universities attached to the Oriente Chapter, and the Faculty of Administrative, Economic and Accounting Sciences of the University of Santander (UDES), have great interest in contributing to the present project to social development and of the region, contributing to higher education institutions strategies to increase attitudes, values ​​and capabilities in the face of entrepreneurship, in future entrepreneurs, as agents of socioeconomic development and with high potential for job creation. In the first phase of the project, the entrepreneurial characteristics of the students are identified and, based on this, the training strategies will be proposed in a second phase. Later, in the third phase the effects of the implementation of the aforementioned strategies will be evaluated, in response to the objectives and principles of the Law of Promotion of the Culture of Entrepreneurship. Because the academic-research community is involved, the results are expected to impact the region by stimulating productive activity with the creation and sustainability of competent companies. The application of the information collection instrument is made to students of the different universities of the Oriente Chapter.